2005
DOI: 10.1097/01.fjc.0000154374.88283.15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Blocking Action of Dihydropyridine Ca2+ Antagonists on a T-Type Ca2+ Channel (α1G) Expressed in Xenopus Oocytes

Abstract: Recent reports show that efonidipine, a dihydropyridine Ca2+ antagonist, has blocking action on T-type Ca2+ channels, which may produce favorable actions on cardiovascular systems. However, the effects of other dihydropyridine Ca2+ antagonists on T-type Ca2+ channels have not been investigated yet. Therefore, in this study, we examined the effects of dihydropyridine compounds clinically used for treatment of hypertension on a T-type Ca2+ channel subtype, alpha1G, expressed in Xenopus oocytes. These effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…18,19 However, it has been reported that the antiproteinuric effects of T-type CCBs are not mediated by angiotensin II inhibition but by blockade of T-type Ca channels in the glomerular arterioles. 6 Furukawa et al 20 surveyed the blocking activity of various CCBs on L-/T-/N-type Ca current in Xenopus oocytes. Although both benidipine and amlodipine exhibited blocking function on both L-and T-type Ca channels, benidipine predominantly blocked the T-type Ca channel, whereas amlodipine predominantly blocked the L-type Ca channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 However, it has been reported that the antiproteinuric effects of T-type CCBs are not mediated by angiotensin II inhibition but by blockade of T-type Ca channels in the glomerular arterioles. 6 Furukawa et al 20 surveyed the blocking activity of various CCBs on L-/T-/N-type Ca current in Xenopus oocytes. Although both benidipine and amlodipine exhibited blocking function on both L-and T-type Ca channels, benidipine predominantly blocked the T-type Ca channel, whereas amlodipine predominantly blocked the L-type Ca channel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the concentration required for benidipine to exert the inhibitory effect on T-type Ca channels can be achieved at clinically relevant doses of benidipine used for the treatment of hypertension. 20,21 Therefore, benidipine, an L-/T-type CCB, should offer additive benefits over CCB-inhibiting L-type Ca channels, but not T-type Ca channels. Furthermore, T-type Ca channels are distributed in the cardiac sinus node and are closely associated with pacemaking potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Efonidipine antagonizes both T-and L-type Ca 2+ channels with similar affinity and has little effect on the N-, P/Q-, and R-type Ca 2+ channels. On the other hand, nifedipine and nilvadipine antagonize only the L-type channels and have lit-tle effect on the other types of Ca 2+ channels (8,9). Hence, we compared efonidipine, nifedipine and nilvadipine with regard to their characteristic action of T-type Ca 2+ channel antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…The renoprotective effects of angiotensin receptor blockers (ARBs) and angiotensinconverting enzyme inhibitors (ACEIs) have been demonstrated (2-4). As a result, both have been recommended as (8,9) by the blockade of T-and L-type calcium channels (10,11), both of which exist at the site of the efferent artery (12). In this study, we evaluate the effects of two different therapeutic strategies using ARBs and benidipine on BP and urinary albumin excretion (UAE), as well as the costeffectiveness of each, in hypertensive patients with albuminuria.…”
Section: Introductionmentioning
confidence: 99%